SUSTAINABLE MARKETING STRATEGY IN STREET COFFEE MSMES: ANALYSIS OF PURCHASE DECISIONS AND IMPLICATIONS FOR THE SDGS - Diana Eravia; Ranti Amelia Utami (Jurnal Al-Iqtishad, 2026)
This study examines sustainable marketing strategies for street coffee MSMEs by examining the role of brand image mediation in the relationship between product quality and purchasing decisions within the framework of the SDGs. The research was conducted at Kopi Saka, a street coffee SME with 17 outlets in Pekanbaru, Indonesia. A quantitative survey was used, and data from 100 respondents were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4. The results showed that all measurement indicators met the convergent validity criteria, with an external load value above 0.70. Product quality positively influences purchasing decisions (β = 0.502) and greatly influences brand image (β = 0.839). Brand image also had a positive impact on purchasing decisions (β = 0.385). The indirect effect of product quality on the purchase decision through brand image was 0.323, with a total effect of 0.825 and a VAF of 39.2%, indicating partial mediation. This model explains 70.4% of brand image variance and 72.4% of purchase decision variance. The findings imply that street coffee MSMEs can strengthen sustainable competitiveness by maintaining consistency in product quality and translating it into a credible brand image, supporting SDG 8, SDG 12, and SDG 17. Keywords: This study examines sustainable marketing strategies for street coffee MSMEs by examining the role of brand image mediation in the relationship between product quality and purchasing decisions within the framework of the SDGs. The research was conducted at Kopi Saka, a street coffee SME with 17 outlets in Pekanbaru, Indonesia. A quantitative survey was used, and data from 100 respondents were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4. The results showed that all measurement indicators met the convergent validity criteria, with an external load value above 0.70. Product quality positively influences purchasing decisions (β = 0.502) and greatly influences brand image (β = 0.839). Brand image also had a positive impact on purchasing decisions (β = 0.385). The indirect effect of product quality on the purchase decision through brand image was 0.323, with a total effect of 0.825 and a VAF of 39.2%, indicating partial mediation. This model explains 70.4% of brand image variance and 72.4% of purchase decision variance. The findings imply that street coffee MSMEs can strengthen sustainable competitiveness by maintaining consistency in product quality and translating it into a credible brand image, supporting SDG 8, SDG 12, and SDG 17. Keywords: Marketing Strategy Brand Image, Product Quality, Purchasing Decisions, SDGs, MSMEs